ANALISIS DISIPLIN KERJA PEGAWAI DI POLTEKKES KEMENKES SURAKARTA - Jaya, Deddy Satriya; Marsudi, Hidup (Surakarta Management Journal, 2024)
The purpose of the study was to find out the description of employee discipline in the Poltekkes Kemenkes Surakarta and what the obstacles were to employee discipline in the Poltekkes Kemenkes Surakarta. The research method uses a qualitative approach with descriptive research types. Data is collected by data sources for informants. Using interview data collection techniques and documentation. Data analysis used descriptive analysis, namely a description in the form of a description, to explain the answers given by respondents. The data obtained through interviews and literature was used as supporting data to strengthen and deepen the results obtained. The results showed that the work discipline of employees at Poltekkes Kemenkes Surakarta had gone well. The obstacle to employee work discipline at the Surakarta Ministry of Health Polytechnic is at the attendance level because employee attendance uses a finger print system that cannot be engineered and the machines that regulate it. Efforts to overcome obstacles to employee work discipline at the Ministry of Health's Surakarta Health Polytechnic are starting from collecting monthly attendance report data, providing verbal and written sanctions, withholding meal allowances and other punishments. To ensure employee attendance data is recorded quickly, in detail and accurately, what is needed is an attendance machine called a finger print.